Prevalence of reducing carbohydrate intake and fasted training in elite endurance athletes and association with bone injury - Raleigh, C.; Madigan, S.; Sinnott-O`Connor, C.; Sale, C.; Norton, C.; Carson, B. P. (European Journal of Sport Science, 2024)
There are conflicting reports both within the lay media and scientific literature regarding the use and benefit of dietary practices that aim to reduce CHO intake in endurance athletes. This study aimed to determine the prevalence of intentional reduction of CHO intake and fasted training in elite endurance-based athletes using a semi-quantitative questionnaire. Bone is a nutritionally modulated tissue; therefore, this study also aimed to explore if these dietary practices are potentially associated with bone injury incidence. The reported reduction of CHO intake was prevalent (28%) with the primary motivation being maintenance or manipulation of body composition. However, discrepancies in athletes' awareness of CHO intake were identified providing a potential avenue of intervention especially within applied practice. The use of fasted training was more prevalent (38%) with athletes using this practice for both body composition manipulation and promoting a desired adaptive response. Forty-four per cent of participants had suffered a radiographically confirmed bone injury at some point in their career. There was no association between reduction in CHO intake and bone injury incidence; however, the incidence of bone injury was 1.61 times higher in those who currently use fasted training compared to those who have never used it or who have used it in the past. Although a direct causal link between these dietary practices and the incidence of bone injury cannot be drawn, it provides robust justification for future investigations of the potential mechanisms that could explain this finding.